2014
DOI: 10.1007/s11357-014-9633-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of the alveolar lining fluid in the aging lung

Abstract: As we age, there is an increased risk for the development of pulmonary diseases, including infections, but few studies have considered changes in lung surfactant and components of the innate immune system as contributing factors to the increased susceptibility of the elderly to succumb to infections. We and others have demonstrated that human alveolar lining fluid (ALF) components, such as surfactant protein (SP)-A, SP-D, complement protein C3, and alveolar hydrolases, play a significant innate immune role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 70 publications
8
140
3
Order By: Relevance
“…Secondly, accumulation of cell debris and increased levels of pro‐inflammatory cytokines TNF‐α and IL‐6, surfactant proteins and lipids (e.g., SP‐A and SP‐D) and several complement components has been observed in aged lungs with a relatively oxidized tissue microenvironment in both mice and humans. This may modify mucosal immune responses in the elderly population (Moliva et al, ). Thirdly, systemic changes in metabolic and hormonal signals likely contribute to the development of chronic inflammation in the aged (Oishi & Manabe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, accumulation of cell debris and increased levels of pro‐inflammatory cytokines TNF‐α and IL‐6, surfactant proteins and lipids (e.g., SP‐A and SP‐D) and several complement components has been observed in aged lungs with a relatively oxidized tissue microenvironment in both mice and humans. This may modify mucosal immune responses in the elderly population (Moliva et al, ). Thirdly, systemic changes in metabolic and hormonal signals likely contribute to the development of chronic inflammation in the aged (Oishi & Manabe, ).…”
Section: Discussionmentioning
confidence: 99%
“…[86]) more total PC in lung lavage than young dogs which also depended on dog strain [30]. Furthermore, inflammatory cytokines and SPs lipids in humans and mice were found to be significantly altered in the aged lung [103]. Alterations in surfactant lipid composition are predicted to negatively affect SP function [152].…”
Section: Alveolar Lining Fluidmentioning
confidence: 99%
“…Less is known about the aging of the surfactant system. One study found no age dependence [118] while another study reported small but significant changes in the composition of the lining fluid that may also be species dependent [103]. Although lung volume increases but the prestress likely decreases because of the decline in lung elastic recoil pressure in the elderly [79].…”
mentioning
confidence: 99%
“…IL-10 was equivalent to the measurements in younger study subjects. An overall basal increase of pro-inflammatory cytokines is observed with aging 38 . Although we evaluated structures containing proinflammatory cytokines, we observed more IL-10-containing structures, suggesting the predominance of antiinflammation is explained as controlling conditions to suppress and regulate the inflammatory environment in relatively healthy lungs regardless of age.…”
Section: Discussionmentioning
confidence: 99%